Response of nuclear-dissociating shocks to vorticity perturbations - César Huete; Ernazar Abdikamalov (My University, 2019)
In the context of core-collapse supernova explosions, the interaction of standing accretion shocks with upstream vorticity perturbations is investigated by linear theory analysis. The endothermic effect associated to the nuclear dissociation, which takes place right behind the shock wave, affects the amplitude of the perturbations amplified/generated across the front. For upstream disturbances whose characteristic size is much larger than the postshock dissociation layer thickness, the effect of nuclear dissociation can be reduced to that of considering the global endothermic effect that scales with the inflow energy flux. The present study focuses on perturbation fields that are not isotropic, which mimic the perturbations in collapsing convective shells of massive stars. The linear interaction of the shock with bidimensional mono-frequency vorticity perturbations is theoretically addressed, with the limit of highly stretched vortices being analyzed in detail. The exact spatial distribution of the rotational and acoustic perturbations generated in the postshock flow are provided along with the transient evolution of the shock front. It is found that nuclear dissociation contributes to stabilize the shock oscillations, but increases the amplitude of the density perturbations downstream.
Keywords: core-collapse supernova; standing accretion shock; vorticity perturbations; nuclear dissociation; shock stability; density fluctuations